Antirheumatic Drugs : Mechanisms, Therapeutic Efficacy, and Clinical Considerations in Rheumatoid Arthritis (International Journal of Scientific Research in Science and Technology, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes inflammation and damage to joints and other tissues. Antirheumatic drugs, including disease-modifying antirheumatic drugs (DMARDs), biologic agents, and non-steroidal anti-inflammatory drugs (NSAIDs), play a crucial role in the treatment and management of RA. This review examines the mechanisms of action, clinical efficacy, and adverse effects of these drugs. We also explore emerging therapies and future directions for RA management, highlighting the importance of individualized treatment strategies to improve patient outcomes while minimizing potential risks.